2012
DOI: 10.1080/87568225.2012.685857
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Wait Time After Triage and Show Rate for Intake in a Nonurgent Student Population

Abstract: Ideally, students requesting services should be seen quickly at their university counseling center to increase the likelihood of a successful treatment outcome. However, in these times of ever-increasing demand for university counseling services and the challenges of securing resources to keep up with that demand, the reality of prompt appointments can be far different during most of the academic year. This study looked at the relationship between wait time after triage and show rate for intake at a large coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…All data are self-reported and cross-sectional, including the retrospective estimate of days waited to begin counseling after triage. It should be noted that the self-reported mean wait time of 15 days for this UCC sample was very consistent with the record-based 16-day mean wait time, using a separate prior sample at the same UCC, reported by DiMino and Blau (2012). One-item measures for mental distress level and wait bother experience do not allow for calculating reliability estimates.…”
Section: Study Limitationsmentioning
confidence: 78%
See 2 more Smart Citations
“…All data are self-reported and cross-sectional, including the retrospective estimate of days waited to begin counseling after triage. It should be noted that the self-reported mean wait time of 15 days for this UCC sample was very consistent with the record-based 16-day mean wait time, using a separate prior sample at the same UCC, reported by DiMino and Blau (2012). One-item measures for mental distress level and wait bother experience do not allow for calculating reliability estimates.…”
Section: Study Limitationsmentioning
confidence: 78%
“…Alternative strategies to "hold" these clients after triage and until intake (Kitzrow, 2009) may be necessary (e.g., psychoeducational groups, drop-in counseling, self-help centers). Prior research has shown that a longer wait time after triage led to a higher no show rate at intake (DiMino & Blau, 2012). However, DiMino and Blau (2012) did not measure wait experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millennial college students have been stereotyped as "typically impatient, want-it-now" (Rickes, 2009). Prior research has shown that as wait time increased between triage and intake, clients were less likely to show up for the scheduled intake (DiMino & Blau, 2012).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Kopta et al (2014) In order to "hold" non-urgent triaged clients to increase their show-rates for their intake session, experimenting with such strategies, as a self-help center and group counseling may be helpful. Follow-up with no-shows to find out why they did not come to intake (DiMino & Blau, 2012) may also be helpful (e.g., used other coping resources, problem resolved, gave up waiting).…”
Section: Implications For Practicing College Clinicians and Resourcinmentioning
confidence: 99%